2017
DOI: 10.2147/ceor.s69340
|View full text |Cite
|
Sign up to set email alerts
|

Home hemodialysis: a comprehensive review of patient-centered and economic considerations

Abstract: Internationally, the number of patients requiring treatment for end-stage kidney disease (ESKD) continues to increase, placing substantial burden on health systems and patients. Home hemodialysis (HD) has fluctuated in its popularity, and the rates of home HD vary considerably between and within countries although there is evidence suggesting a number of clinical, survival, economic, and quality of life (QoL) advantages associated with this treatment. International guidelines encourage shared decision making b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 86 publications
1
75
0
2
Order By: Relevance
“…PD outcomes over the first 3 years of dialysis therapy are superior to those of CHD . Home‐based dialysis can allow for more freedom for patients to make their own lifestyle choices, especially as it relates to employment, hobbies, and family time, improving quality of life . Several studies have reported that 90% or more of nephrologists and other dialysis health care providers would select home therapies for themselves if they required dialysis .…”
Section: Current State Of Dialysis Modalities In the United States Anmentioning
confidence: 99%
“…PD outcomes over the first 3 years of dialysis therapy are superior to those of CHD . Home‐based dialysis can allow for more freedom for patients to make their own lifestyle choices, especially as it relates to employment, hobbies, and family time, improving quality of life . Several studies have reported that 90% or more of nephrologists and other dialysis health care providers would select home therapies for themselves if they required dialysis .…”
Section: Current State Of Dialysis Modalities In the United States Anmentioning
confidence: 99%
“…HHD uptake by initially under‐represented portions of the community may have improved with intentional clinical advocacy, education and addressing of financial barriers to HHD. Recent studies in the NZ population have identified a lack of confidence, fear of isolation, fear of self‐needling and financial constraints as key barriers to HHD uptake . Additionally, clinician recommendation has a significant impact on decision making around the modality choice, with several recent studies confirming that recommendation from an engaged nephrologist is a prime factor in patients choosing home haemodialysis .…”
Section: Discussionmentioning
confidence: 99%
“…Trainee parents can talk to parents with children already on an HHD program which would reinforce their confidence in caring for their children at home. In addition, strong recommendations and support from the clinicians, home HD support staff, incorporation of remote monitoring, or after‐hours support systems can also help attenuate these fears …”
Section: Barriers Of Home Hemodialysismentioning
confidence: 99%
“…Overcrowding, lack of space for storage of dialysis consumables, lack of hygienic or a private room for dialysis, and inappropriate home environment are noteworthy obstacles to starting HHD. Another challenge is for people living in rental homes, where owing to lack of permission from the homeowners, the required plumbing and electrical changes cannot be made …”
Section: Barriers Of Home Hemodialysismentioning
confidence: 99%